Evangeljsko žensko društvo v Ljubljani 1856-1945 - Serše, Aleksandra (Etnolog. Nova vrsta (Ljubljana), 2001)
The article is based on the archive material kept by the Archives of the Republic of Slovenia and the Historical Archives of Ljubljana. It presents the activities of the oldest women's society established in Ljubljana - the philanthropic Evangelical Women's Society called Evangeljsko žensko društvo (German: Evangelischer Frauenverein Laibach) which operated in Ljubljana from 1856 until 1945.
Keywords: Ljubljana; kulturna zgodovina; woman; ženske; association; društva; dobrodelnost; evangeličani; Evangelijsko žensko društvo v Ljubljani